2012
DOI: 10.1007/s11145-012-9401-8
|View full text |Cite
|
Sign up to set email alerts
|

Persisters and nonpersisters: Identifying the characteristics of who stays and who leaves from adult literacy interventions

Abstract: Adult literacy programs are characterized by high attrition rates. Rigorous exploration of student persistence in adult reading classes is lacking. This study was an attempt to understand the profiles of adults who completed reading classes compared to a group of adults who made it to the midpoint and a group of adults who did not make it to the midpoint. Students were offered 100 hours of instruction. Of the 395 students who attended the first day of class, only 198 completed the program. Results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
4
13
0
Order By: Relevance
“…Research results are mixed with respect to the influence of age on success in LBS programs. Several studies have suggested that older students are more successful than younger students in LBS programs (Greenberg et al, 2013), while other studies have indicated that age may be a barrier to success (Zacharakis et al, 2011). Smith and Smith (2008) reported that the odds of LBS students engaging in asynchronous learning activities increased by 1-2% with each year of age.…”
Section: Individual Differences Lbs Programs and Blended Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Research results are mixed with respect to the influence of age on success in LBS programs. Several studies have suggested that older students are more successful than younger students in LBS programs (Greenberg et al, 2013), while other studies have indicated that age may be a barrier to success (Zacharakis et al, 2011). Smith and Smith (2008) reported that the odds of LBS students engaging in asynchronous learning activities increased by 1-2% with each year of age.…”
Section: Individual Differences Lbs Programs and Blended Learningmentioning
confidence: 99%
“…This study and its research questions are grounded in a conceptual framework found in the research literature as reviewed above. The literature-based framework demonstrates that: (a) learner attitudes toward blended learning (Ausburn, 2004;Fisher & Baird, 2005;Gill, 2009;Gülbahar & Madran, 2009), the effects of blended learning (Ashby et al, 2011;Fenouillet & Kaplan, 2009) and perceived academic successes can be identified (Gonzalez, 2014;Rovai & Jordan, 2004); (b) blended learning can be related to perceived learning success (Boyle et al, 2003;Giguere, 2009); and (c) individual learner differences can be related to variations in their attitudes toward blended learning (Greenberg et al, 2013;Pross & Barry, 2004;Smith & Smith, 2008;Sorden & Munene 2013). This framework supports the choices of the independent and dependent variables for this study and the relationships proposed among them by the research questions.…”
Section: Research Questions and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…High drop-out rates are associated with younger age, worse blending, slower naming, and comprehension skills, as well as increased avoidance of reading difficult materials. Furthermore, current/past enrollment in ABE classes increased the probability of midpoint completion (Greenberg et al, 2012). Therefore, the programs should pay more attention to the participants that fall within these categories.…”
Section: Who Is Defined As Functional Illiterate?mentioning
confidence: 99%
“…With regard to skill improvement, outcomes in three of the studies were associated with differences in the initial reading skill level of older learners (Calhoon and Petscher, 2013;Greenberg et al, 2012;Scarborough et al, 2012). Additionally, two of the adults studies found differences associated in demographics characteristics of students who maintained enrollment and those who dropped out (Greenberg et al, 2012;Mellard et al, 2012).…”
mentioning
confidence: 96%